2023
DOI: 10.3389/fragi.2023.1057204
|View full text |Cite
|
Sign up to set email alerts
|

Towards AI-driven longevity research: An overview

Abstract: While in the past technology has mostly been utilized to store information about the structural configuration of proteins and molecules for research and medical purposes, Artificial Intelligence is nowadays able to learn from the existing data how to predict and model properties and interactions, revealing important knowledge about complex biological processes, such as aging. Modern technologies, moreover, can rely on a broader set of information, including those derived from the next-generation sequencing (e.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 127 publications
0
7
0
Order By: Relevance
“…In the present study, a higher blood biological age was associated with high SB and a trend of low PA. The ageing clock technology is currently being used in various products for health screening and is at the foundation of the emerging longevity medicine field [36,37]. Additionally, ageing clocks are widely used in anti-ageing research and are actively being patented for commercial applications [38,39].…”
Section: Association Of Blood Biological Age With Objectively Measure...mentioning
confidence: 99%
“…In the present study, a higher blood biological age was associated with high SB and a trend of low PA. The ageing clock technology is currently being used in various products for health screening and is at the foundation of the emerging longevity medicine field [36,37]. Additionally, ageing clocks are widely used in anti-ageing research and are actively being patented for commercial applications [38,39].…”
Section: Association Of Blood Biological Age With Objectively Measure...mentioning
confidence: 99%
“…Currently, AI technologies for aging population are used in the robotic intervention ( 80 , 81 ), applications on smartphones or computers ( 82 , 83 ), social interaction and support, such as improved mental well-being and quality of life ( 84–86 ); rehabilitation therapy, such as its application in the recovery of upper and lower extremity functions, gait robotic rehabilitation, or improve sleep quality and daily living activities ( 87–90 ), and wearables, voice-activated ( 91–94 ). It can create more advanced algorithms to provide more precise holistic interventions tailored to address the elders’ multiple needs in a safer and more friendly manner ( 78 , 95 , 96 ). Ambient-assisted working and ambient-assisted living are examples of smart systems that can adapt themselves to older adult needs by exploiting ambient intelligence solutions.…”
Section: Ai In Population Agingmentioning
confidence: 99%
“…These systems focus on using technology to support and enhance the quality of life of the older adult population, either in work, or indoor and outdoor environments ( 97 , 98 ). Recently, a group of researchers have helped develop drugs that might potentially delay the effects of aging by eliminating senescent cells ( 96 , 99 ).…”
Section: Ai In Population Agingmentioning
confidence: 99%
“…Moreover, artificial intelligence (AI)-driven platforms, such as PandaOmics, have facilitated the identification and prioritization of novel aging-associated targets for drug discovery and repurposing [7]. Recent studies have also demonstrated the value of AI in advancing longevity research by harnessing the power of nextgeneration sequencing data and omics technologies [8]. AGING Insilico Medicine has been at the forefront of using generative AI in biology since 2016 [9][10][11].…”
Section: Introductionmentioning
confidence: 99%